Handbook of Magnetic Measurements - Tumanski, Slawomir (Boca Raton : CRC Press, 2011)
While magnetic devices are used in a range of applications, the availability of up-to-date books on magnetic measurements is quite limited. Collecting state-of-the-art knowledge from information scattered throughout the literature, Handbook of Magnetic Measurements covers a wide spectrum of topics pertaining to magnetic measurements. It describes magnetic materials and sensors, the testing of magnetic materials, and applications of magnetic measurements.Suitable for specialists as well as readers with minimal knowledge of magnetic measurements, the book begins with an easy-to-follow introduction to the essentials of magnetic measurements. It then offers a comprehensive review of various modern magnetic materials, such as soft and hard magnetic materials and thin magnetic films. The text also describes all commonly used magnetic field sensors, including inductive, fluxgate, Hall, magnetoresistive, resonance, SQUID, magnetoelastic, and magnetooptical sensors. The final chapters discuss the nondestructive testing of materials and explore applications related to magnetic measurements, including magnetic diagnostics in medicine, magnetoarcheology, and magnetic imaging.A thorough overview of magnetic measurements, this handbook helps readers navigate the sometimes impenetrable terms of the field. It also assists them in the quest to design electromagnetic devices in a more effective way--
1. Introduction to magnetic measurements -- 2. Fundamentals of magnetic measurements -- 3. Magnetic materials -- 4. Magnetic sensors -- 5. Testing of magnetic materials -- 6. Magnetic field measurements and their applications.
A Taylor & Francis book.
Keywords: Magnetic materials -- Testing; Magnetic measurements; Electronic books